Characterization of metakaolin-based materials for dye adsorption from aqueous solution - Narumon Lertcumfu (2018)
© 2018 Trans Tech Publications, Switzerland. The properties of metakaolin-based materials were investigated. The studied materials were prepared by mixing metakaolin and aluminum oxide in alkaline solution. The obtained samples were cast into plastic molds and then left at 27o C for 24 h. The properties of the materials were investigated using XRD, FTIR, and SEM. The obtained results suggested that reaction of the mixed materials occurred. The adsorption properties of the materials, including removal efficiency, distribution coefficient, and uptake capacity were determined. The obtained results revealed that the studied materials exhibited high adsorption capacity, which is good for the adsorbent applications.